The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1993
DOI: 10.1161/01.hyp.21.5.660
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin blockade reverses hypertension during long-term nitric oxide synthase inhibition.

Abstract: Blockade of the renin-angiotensin system was studied in male Sprague-Dawley rats during long-term inhibition of nitric oxide synthase. Nitro-L-arginine-methyl ester (L-NAME) was placed in the drinking water for 4 weeks (-100 nig/kg per day). Separate groups of rats were coadministered the angiotensin II antagonist A-81988 in the drinking water ranging from approximately 0.001 to 1 ing/kg per day. Control groups received only tap water or A-81988 alone. Each week, rats were placed in metabolic cages, and tail-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
95
3

Year Published

1996
1996
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(113 citation statements)
references
References 15 publications
15
95
3
Order By: Relevance
“…However, there is evidence that the renin-angiotensin system is largely responsible for renal and systemic alterations when NO synthesis is reduced. Chronic AT 1 receptor blockade or converting enzyme inhibition prevents the development of hypertension after L-NAME (6). Furthermore, the L-NAME-induced BP increase was completely reversed by AT 1 receptor blockade in both AT 2 Ϫ/Ϫ and AT 2 ϩ/ϩ mice, underscoring the importance of the AT 1 receptor for BP changes after L-NAME.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…However, there is evidence that the renin-angiotensin system is largely responsible for renal and systemic alterations when NO synthesis is reduced. Chronic AT 1 receptor blockade or converting enzyme inhibition prevents the development of hypertension after L-NAME (6). Furthermore, the L-NAME-induced BP increase was completely reversed by AT 1 receptor blockade in both AT 2 Ϫ/Ϫ and AT 2 ϩ/ϩ mice, underscoring the importance of the AT 1 receptor for BP changes after L-NAME.…”
Section: Discussionmentioning
confidence: 81%
“…Furthermore, L-NAME treatment reduced in AT 2 ϩ/ϩ mice renal AT 1 receptor expression, whereas the AT 1 receptor expression in AT 2 Ϫ/Ϫ mice was not significantly changed. L-NAME application produces an AngII-dependent form of hypertension (6). The physiologic results on sodium and water reabsorption and renal hemodynamic may have been aggravated in AT 2 Ϫ/Ϫ mice by the deletion of the AT 2 receptor and the upregulation of the AT 1 receptor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10,12 It has recently been shown that the modulation of regional blood¯ow in vascular tissues depends in part on a balance between NO and Ang II, and that an imbalance between these substances can result in hypertension. 18,19 Administration of Ang II receptor antagonists has been shown to restore normal blood pressure and normal renal hemodynamics in humans with essential hypertension, as well as in experimental rats with spontaneous hypertension, 20 with hypertension induced by chronic NOS inhibition, 16 and with renovascular hypertensive disease. 21 Our results suggests that, as in conventional vascular tissue, a relative increase in Ang II in the modi®ed vascular tissue of the corpus cavernosum may contribute to erectile dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, nitric oxide (NO) has been reported to be involved in the vasodilator and antihypertensive effects of losartan in different experimental models (Cachofeiro et al, 1992; Kumagai et al, 1993;Pollock et al, 1993;Sudhir et al, 1993) and to modulate sympathetic neurotransmission (Zanzinger et al, 1994). Moreover, in porcine cultured endothelial vascular smooth muscle cells (Jaiswal et al, 1991) and in rabbit vas deferens tissue (Catalioto et al, 1994), losartan has been reported to increase vasodilator prostaglandin (PGs) synthesis and/or release.…”
Section: Introductionmentioning
confidence: 99%